Model Aplikasi Adaptif Rencana Anggaran Biaya (RAB) Jalan Desa Berkelanjutan Berbasis Android - Firdausi, Annisa Azhar (MoDuluS Media Komunikasi Dunia Ilmu Sipil, 2025)
The urgency of the Sustainable Development Goals (SDGs) of villages is a global and national commitment in an effort to take action to reduce the impact of climate change and overcome the challenges faced, through the development of sustainable infrastructure that leads to green infrastructure. The application was made to assist the Village Development Activity Planning Team (TPK) in making an android-based Sustainable Village Road Cost Budget Plan (RAB), with K175kg/cm2 and K225kg/cm2 quality paying attention to construction percolation and rainwater infiltration. Testing the adaptive application of the Cost Budget Plan (RAB) for sustainable village roads based on android by inputting the street name, filling in the length, width and thickness of the pavement to be built, then inputting the price of building materials and labor wages based on local prices, after RUN will be able to find out the material needs, costs, and the amount of rainwater infiltration into the soil.